Intertextulaity In Language: The Speech of Ayatollah Ali Sistani as Practical Sample - Farhan Al-Nussairi, Wissam (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The study aims to employ intertextuality in the language. It surveys theconcepts and definitions of intertextuality according to some famouslinguistic experts. The study gives a precise summary about intertextualityand the relation between discourse and intertextuality. The studyexplores types of intertextualities and refers to its subdivisions. The studyincludes an analysis part in addition to the theoretical side. The analysis isfocused on a speech made by Ayatullah Ali Al_sistani. The analysiskeened on intertextuality in that text and types of intetextuality that areadopted by the speaker . The study reached the conclusion that thespeech was full with direct quotation for specific explanation. The oratorfollowed this strategy to make his audience more experienced about he isoriented for. The study concludes that most texts are full of intertextuality.Political and religious texts are full with direct quotations for specific goals.